12 - Love, Sex and Gender: Missing in African Child and Youth Studies - Bhana, Deevia (Africa Development, 2017)
In African childhood studies, ideas about love, sex and gender are often ignored. Despite love’s overarching presence children and young people are often written about as loveless. The study of African childhood sexualities, its gendered effects and the local configurations of power and affects, remains an embryonic field of study. Under the surveillance of sexual violence, disease and girls’ particular vulnerability across Africa, much of the scholarship has remained concerned with children as victims and cast within the frame of a suffering sexuality. This article seeks to break from the tendency that ignores love, sex and gender in African children’s intimate relations. By drawing on empirical research conducted with children and young people in South Africa, the article demonstrates how boys and girls negotiate and invest in intimacy under varying social conditions. In doing so it hopes to address this missing dimension in African research to reconfigure love, gender and sexuality as a critical part of young people’s lives in Africa. In addressing young Africans as active agents in constructing sexualities and their investments in affective dimensions of relationships, the article seeks to arrive at a way of making childhood sexualities as critical to building a fuller account of African childhoods. In doing so this article radically calls into questions studies that curtails sexualities from the studies of children and young people. The article also argues that the benefits of addressing young Africans as sexual with capacities to engender love is important if we are to move beyond the scourge of violence and inequalities and to advance gender-equitable relations in childhood.